ROLE OF ARTIFICIAL INTELLIGENCE IN FINANCIAL MANAGEMENT - Deshmukh, Prajakta B; Nikam, Poonam; Moholkar, Nilambari (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper investigates the role of Artificial Intelligence (AI) in financial management, focusing on finance managers' perceptions and attitudes towards its application. Utilizing a quantitative research methodology, the study explores AI's impact on various facets of financial decision-making processes, risk management, and alignment with organizational goals. The findings reveal a positive perception among finance managers, affirming the significance of AI in revolutionizing financial management practices. Implications suggest the need for organizations to embrace AI technologies, invest in adoption, and promote continuous skill development among managerial staff. The research contributes to the evolving discourse on AI in financial management and sets the stage for future investigations into specific impact areas and challenges.